Digital transformation tools: a case study (National Administration Journal, 2025)
The growing digital transformation demands the implementation of tools to ensure competitiveness in an increasingly innovation-oriented market. The general objective of this research is to analyze the digital transformation process of a company dedicated to the production, promotion, and marketing of sotol products located in Ciudad Juárez, Chihuahua, applying tools such as PESTEL and SWOT to support its market participation and economic growth. The specific objectives established are to describe the characteristics of the digital transformation process, diagnose the current state of digital transformation, and adapt digital transformation tools according to the company's business needs. The findings include best practices, challenges, and specific recommendations.
Keywords: Digital transformation; strategies; marketing